Estimates on state-specific Pneumococcal Conjugate Vaccines (PCV) coverage in the private sector in the year 2012: Evidence from PCV utilization data - Habib Hasan Farooqui; Sanjay Zodpey; Maulik Chokshi; Naveen Thacker (Wolters Kluwer Medknow Publications, 2016)
The pneumococcal conjugate vaccine (PCV) is not available through universal immunization programs but is available through private healthcare providers. Because the PCV coverage rates are unknown, we developed a Microsoft Excel-based coverage assessment model to estimate state-specific PCV coverage for the year 2012. Our findings suggest that in the private sector, the "overall PCV coverage" was around 0.33% that ranged between a minimum of 0.07% for Assam, India and a maximum of 2.38% for Delhi, India. Further, in major metropolitan areas, overall PCV coverage rates were: 2.28% for Delhi, India, 13.31% for Mumbai (Maharashtra), India 0.76% for Lucknow (Uttar Pradesh), India, 1.93% for Kolkata (West Bengal), India, and 4.92% for Chennai (Tamil Nadu), India highlighting that urban centers are major drivers for PCV utilization driver in the states with high PCV consumption. Hence, to improve PCV coverage, both demand side (increasing consumer awareness about pneumonia prevention) and supply side (controlling vaccine prices and indigenous vaccine production) interventions are required.